2013
DOI: 10.1210/jc.2012-2517
|View full text |Cite
|
Sign up to set email alerts
|

Association of Previous Schistosome Infection With Diabetes and Metabolic Syndrome: A Cross-Sectional Study in Rural China

Abstract: The associations between PSI and the lower prevalence of diabetes and a better metabolic profile in rural Chinese need to be confirmed in other populations. If confirmed, the protecting effect of helminth infection could be reconsidered in terms of therapeutic strategies for the treatment of diabetes and metabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(161 citation statements)
references
References 17 publications
10
147
3
1
Order By: Relevance
“…Our finding was somewhat consistent with the results of a crosssectional study conducted in Jiading, a suburb of Shanghai [8], which reported that PSI might reduce the prevalence of diabetes and metabolic syndrome. Additionally, our findings showed that PSI was negatively correlated with TG and positively correlated with HDL-C.…”
supporting
confidence: 92%
“…Our finding was somewhat consistent with the results of a crosssectional study conducted in Jiading, a suburb of Shanghai [8], which reported that PSI might reduce the prevalence of diabetes and metabolic syndrome. Additionally, our findings showed that PSI was negatively correlated with TG and positively correlated with HDL-C.…”
supporting
confidence: 92%
“…People in a rural area in China who have a history of Schistosoma infections compared to endemic controls who never suffered from schistosomiasis had a lower body mass index and fasting blood glucose levels, and reduced prevalence of T2D and metabolic syndrome [16]. Accordingly, prevalence of lymphatic filariasis was significantly lower in diabetic subjects than nondiabetic subjects in Chennai, India [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recent cross-sectional studies in India, Indonesia, rural China, and in aborigines in Australia revealed that the prevalence of helminth infections in T2D patients is significantly lower than in nondiabetic controls, independent of socioeconomic differences in income and nutrition, suggesting that helminth infections may indeed prevent or delay the onset of T2D [15,16,17,18]. Possible helminth-mediated protective mechanisms include the downregulation of proinflammatory immune responses that are associated with T2D, the induction of type 2 immune responses, the promotion of fatty acid uptake, or a stronger expression of genes that are associated with insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements of triglycerides, total cholesterol, low‐density lipoprotein cholesterol and high‐density lipoprotein cholesterol were carried out using an enzymatic colorimetric method (LX‐20; Beckman, Brea, CA, USA) by the Shanghai Institute of Endocrinology and Metabolism; and the measurement of HbA1c was carried out by a high‐performance liquid chromatography method (Bio‐Rad Laboratories, Hercules, CA, USA)22.…”
Section: Methodsmentioning
confidence: 99%